Income support systems, labour supply incentives and employment: Some cross-country evidence - Anders Forslund; Peter Fredriksson (Institute for Labour Market Policy Evaluation (IFAU), 2009)
This paper summarizes a set of expert reports commissioned by the IFAU. The expert reports cover Estonia, Germany, Italy, the Netherlands, Sweden, and the United Kingdom. These countries represent range of welfare states, both in terms of scope and design. And in each country there are interesting experiences from which other countries may learn. The overall objective is to identify policy tools that help generate sustained increases in employment in the long run. Therefore, we focus on policies that improve the incentives for labour force participation and reduce the barriers to participation.
Keywords: J08; J21; 330; Labour force participation; employment; income support; long-run sustainability; Arbeitsmarktpolitik; Soziale Sicherung; Beschäftigung; Erwerbstätigkeit; Deutschland; Estland; Großbritannien; Italien; Niederlande; Schweden